Transnational Female Solidarity and Gender Equality in the Comic Medium: Pepita Sandwich's Las mujeres mueven montañas and Ana Penyas's Estamos todas bien. Issue 6 (1st June 2022) - BRITLAND, JOANNE
Abstract : This essay explores how the comic medium fosters transnational, female empowerment and solidarity through the analysis of two graphic novels written by artists from opposite sides of the Atlantic. Las mujeres mueven montañas (2019), by Pepita Sandwich (Josefina Guarracino, Argentina), traces the accomplishments of fourteen exceptional women throughout recent history. The second narrative, Estamos todas bien (2017), by Ana Penyas (Spain), describes the lives of two women, Penyas's grandmothers, who lived in Spain under the Franco dictatorship. By drawing upon theories of memory studies and the comic as a form of documentary and testimony, this essay demonstrates how these graphic narratives provide a platform that creates a unified genealogy of women across the globe through the retelling of the past.